Map literacy and spatial cognition challenges for student geography teachers in South Africa - Larangeira, Rhoda; Van der Merwe, Clinton David (Faculty of Education, University of the Free State, 2016)
South African geography student teachers should master map skills to teach mapwork effectively in their future classrooms. Spatial cognition, prior learning of map skills and map interpretation at secondary school-level are highlighted as being important in furthering map literacy, which is required by geography student teachers. A mixed-method research framework investigated the causes of map literacy difficulties experienced by first year geography student teachers. Lecturers who train prospective teachers should be aware of the conceptual and/or skills-based difficulties associated with poor map literacy amongst their own students in order to address these problems. This paper outlines problems experienced by first year geography student teachers associated with their own acquisition and understanding of mapwork. Furthermore, it argues that without deeper comprehensive development of their own mapwork content knowledge, the geography student teachers’ ability to teach map skills effectively will be adversely affected.
Keywords: Curriculum Assessment Policy Statement (CAPS); Geography student teachers; Map literacy; Prior learning; Secondary education; Spatial cognition